EFFECT OF TRAINING ON CAREER PERFORMANCE OF NIGERIA SECURITY AND CIVIL DEFENSE CORPS (NSCDC) PERSONNEL IN KADUNA STATE COMMAND - LEKSHUM SUNDAY AMOS (International Studies Journal)
This paper examines the effect of training on career performance of Nigeria Security and Civil Defense Corps (NSCDC) Personnel in Kaduna state command to examine the impact and types of training required for effective career performance of NSCDC personnel. Specific training programmes examined were Basic Training, Intermediate and advanced training. Four hypotheses were formulated for the study. A sample of 200 NSCDC personnel from 5 divisional offices was selected for the study through simple random sampling technique. The instrument for data collection was a questionnaire titled 'Effect of Training and Performance Questionnaire (ETPQ) developed by the researcher. It was subjected to the scrutiny of three experts in the in the department of Sociology, Ahmadu Bello University, Zaria for Validation. The reliability of the instrument was determined by a pilot study using 30 respondents who were not part of the main study, respondents were entered into the statistical packages for the social sciences (SPSS) Version 21. The reliability of the instrument yielded 82 correlation coefficients crouchback Alpha, Data collected were analyzed using descriptive statistics (frequencies percentages mean and standard deviation) for demographic characteristics of respondents, one sample t-test and one[1] way analysis of variance (ANOVA) were used to test research hypotheses at 0.05 level significance. Findings revealed that basic training has significance positive effect on the career performance of NSCDC personnel in Kaduna state command. Findings also revealed that intermediate and advanced training programmes have significance positive effect on the career performance of NSCDC personnel in Kaduna state command. There was no significant difference in the mean scores of training programmes and effect on career performance of NSCDC personnel in Kaduna Command. It concluded that training (basic intermediate and advanced training) can improve the career performance of NSCDC personnel. It recommended among others that the NSCDC as a security organization should organize training on regular basis to improve the career performance of personnel of their organization in view of the current security challenges facing the country.